Synergistic A-site co-doping of (Na1/2Bi1/2)xBa1−xZn1/3Nb2/3O3 perovskites: doping mechanisms, microstructure and impedance studies - Y. Feng; A.T.Z. Lim; M. Lu; J. Sun; K.Y. Chan; S. Ghotekar; D. Zhou; D.C. Sinclair; K.B. Tan (Journal of Science: Advanced Materials and Devices)
This study explores the novel synergistic co-doping of (Na1/2Bi1/2)2+ ions into the A-sites of Ba(Zn1/3Nb2/3)O3 (BZN) perovskites to optimise dielectric properties and reduce sintering temperatures. Polycrystalline (Na1/2Bi1/2)xBa1−xZn1/3Nb2/3O3 ceramics (x = 0.1–0.4) were synthesised via solid-state reaction, achieving dense microstructures with relative densities exceeding 92 %. The presence of Na0.13Bi1.87O2.87 and ZnNb2O6 transient phases facilitated a significant reduction in sintering temperature from 1200 °C (x = 0.1) to as low as 950 °C (x = 0.4). XRD, Rietveld refinement and TEM confirmed the formation of phase-pure cubic perovskites with Pm 3‾ m symmetry. Dielectric studies revealed enhanced room-temperature relative permittivity (ε′) and optimised dielectric loss (tan δ), attributed to dipole polarisation induced by 6s2 lone-pair electrons of Bi3+ and improved grain size. Notably, the composition, x = 0.2 exhibited the lowest tan δ (∼0.0096 at 1 MHz) and highest electrical resistance, representing the optimal balance of dielectric performance. Impedance spectroscopy analysis revealed grain-dominated electrical processes and reduced oxygen vacancies, thereby corroborating the correlation between composition, microstructure and electrical properties. This work highlights the functionality of (Na1/2Bi1/2)2+ co-doping to enhance the dielectric performance of BZN perovskites while achieving optimal density at reduced sintering temperatures, thus rendering them suitable for applications in Low-Temperature Co-Fired ceramic (LTCC) for advanced electronic devices.